2022
DOI: 10.1007/s12274-021-3999-2
|View full text |Cite
|
Sign up to set email alerts
|

Operando electrochemical SERS monitors nanoparticle reactions by capping agent fingerprints

Abstract: Nanomaterials are frequently employed in daily life goods, including health, textile, and food industry. A comprehensive picture is lacking on the role of the capping agents, added ligand molecules, in case of nanoparticle reactions and degradation in aqueous solutions, like surface waters or biofluids. Here, we aim to elucidate the capping agent influence on nanoparticle reactivity probing two commonly employed capping agents citrate and polyvinylpyrrolidone (PVP). Their influence on silver nanoparticle (AgNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Figure 1a presents the spectral changes as a function of the applied potential during the dealloying of AgAuNPs on Pt WE. At a potential of −0.2 V, the characteristic Raman bands of the citrate-capped AgAuNPs are detected at 220 cm −1 (νAg−O), 1208 cm −1 (νCCO), and 1619 cm −1 (νCO 2 ), as described in detail in ref 35. The center frequencies of occurring SERS modes are tabulated in Table S1 in the SI.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Figure 1a presents the spectral changes as a function of the applied potential during the dealloying of AgAuNPs on Pt WE. At a potential of −0.2 V, the characteristic Raman bands of the citrate-capped AgAuNPs are detected at 220 cm −1 (νAg−O), 1208 cm −1 (νCCO), and 1619 cm −1 (νCO 2 ), as described in detail in ref 35. The center frequencies of occurring SERS modes are tabulated in Table S1 in the SI.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Au-enriched porous nanoparticles are formed by the electrochemical dissolution of Ag from AgAuNPs in halide-free 250 mM KNO 3 (99.999%) on Pt working electrode (WE) via oxidation of Ag described by the following reaction , Ag ( s ) + NO 3 ( aq ) Ag + ( aq ) + normale + NO 3 ( aq ) Figure a presents the spectral changes as a function of the applied potential during the dealloying of AgAuNPs on Pt WE. At a potential of −0.2 V, the characteristic Raman bands of the citrate-capped AgAuNPs are detected at 220 cm –1 (νAg–O), 1208 cm –1 (νCCO), and 1619 cm –1 (νCO 2 ), as described in detail in ref . The center frequencies of occurring SERS modes are tabulated in Table S1 in the SI.…”
Section: Resultsmentioning
confidence: 86%
“…50 RMHD has also been combined with fluorescence correlation spectroscopy 54 to attain flow profiles and diffusion coefficients of particles down to 0. silver and silica core gold shell (Ag and SiO 2 @Au), in a volume beyond the confines of the microscope's viewing window. Silver 41,55 and silica core gold shell 56,57 were chosen because they are widely studied materials and are frequently used NPs for investigation with DFM and thus serve as excellent model systems for coupled RMHD−DFM. 31 The NP types are detected and differentiated from each other based on the scattered light with blue/green and orange/red wavelengths from their LSPR, respectively, which also allows visualization of the small nanoscopic entities.…”
Section: Introductionmentioning
confidence: 99%
“…LSPR, first described by Faraday in 1857, is based on the interaction of light with nanostructures and determines the color of plasmonic NP suspensions. Because only non-transmitted light is detected in DFM, it is useful for observing individual NPs that exhibit strong LSPRs such as silver, gold, and copper, as well as for monitoring their chemical reactions and events at their surfaces. DFM combined with NP tracking analysis has been previously used to determine their diffusion coefficients by tracing the random paths of NPs in a static suspension . In addition to providing diffusion coefficients, single-particle tracking facilitates detailed observation of how a NP interacts with its surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, SERS has found numerous applications in biomedical research. A simple and efficient strategy for SERS substrate preparation is the aggregation of gold or silver nanoparticles [ 12 , 13 ], with an optional oxidation or electrochemical removal of capping agents for additional signal improvement [ 14 , 15 ]. A recent study revealed the dynamic nature of SERS signal generation in nanoparticle-based substrates [ 16 ].…”
Section: Introductionmentioning
confidence: 99%